The impact of physical exercise on death anxiety in older adults: the chain-mediating role of self-efficacy and psychological resilience - Li, Feixuan; Peng, Jiahui; Zhou, Deqiao (Frontiers in Psychiatry, 2025)
BackgroundWith the rapid global aging trend, understanding death anxiety among the elderly has become a key focus in mental health research. Grounded in a biopsychosocial perspective, this study aims to examine the association between physical exercise and death anxiety in older adults and to explore the potential mediating roles of self-efficacy and psychological resilience within a cross-sectional framework.MethodsUsing a cross-sectional design, the study surveyed 772 Chinese individuals aged 60 and above. Data were collected via the Physical Activity Rating Scale, Death Anxiety Scale, General Self-Efficacy Scale, and Psychological Resilience Scale. Correlation analysis and multiple regression were conducted using SPSS 27.0, and the hypothesized mediating effects were tested using the Bootstrap method in PROCESS 4.0.ResultsPhysical exercise was significantly negatively correlated with death anxiety (r = -0.740, p < 0.01) and was a significant negative correlate in the regression model (β = -0.196, p < 0.001). Self-efficacy (r = -0.827, p < 0.01) and psychological resilience (r = -0.854, p < 0.01) were also strongly negatively correlated with death anxiety. The analyses supported their roles as independent mediators (effect sizes: self-efficacy pathway = -0.1203; resilience pathway = -0.0647). Furthermore, a chain mediation model showed that the sequential pathway through “self-efficacy → psychological resilience” was significant (effect size = -0.1373), accounting for 31.29% of the total indirect effect. Collectively, the three mediation paths explained 73.46% of the total association. Notably, psychological resilience was the strongest negative correlate of death anxiety (β = -0.463).ConclusionOur cross-sectional findings suggest that physical exercise is not only directly associated with lower death anxiety in older adults, but may also be linked through a chain of psychological resources involving self-efficacy and psychological resilience. These findings offer a theoretical basis for future longitudinal and interventional research aimed at constructing integrated “exercise-psychology” intervention models.